The alternations of nucleus accumbent in schizophrenia patients with auditory verbal hallucinations during low-frequency rTMS treatment - Xie, Yuanjun; Cai, Yun; Guan, Muzhen; Wang, Zhongheng; Ma, Zhujing; Fang, Peng; Wang, Huaning (Frontiers in Psychiatry, 2022)
Low-frequency repetitive transcranial magnetic stimulation (rTMS) has been shown to reduce the severity of auditory verbal hallucinations (AVH) and induce beneficial functional and structural alternations of the brain in schizophrenia patients. There is abundant evidence that the nucleus accumbent (NAcc) is implicated with the pathology of schizophrenia. However, the alternations of functional and structural patterns of NAcc in schizophrenia with AVH during low-frequency rTMS are seldom explored. In the present study, we applied resting-state functional connectivity (FC) and structural measure (gray matter volume, GMV) to investigate the functional and structural alternations of NAcc in schizophrenia patients with AVH during 1 Hz rTMS over the left temporoparietal junction. Correlation analyses were further done between the induced functional and structural alternations of NAcc and clinical responses in patients. Group comparison found enhanced FC of NAcc with the temporal lobes (e.g., left middle temporal gyrus, left inferior temporal gyrus, and right fusiform gyrus), while decreased FC of NAcc with the frontal cortices (e.g., right superior frontal gyrus and right inferior frontal gyrus) and anterior cingulate gyrus in the patients at baseline relative to healthy controls. In addition, the reduced GMV of left NAcc was observed in the patient group before treatment compared to the control group. Although low-frequency rTMS did not affect the volumetric changes of NAcc, the abnormal FC patterns of NAcc were normalized or reversed in the patient group after treatment, and the induced FC pattern alternations of NAcc were associated with the improvements in psychotic symptoms (e.g., AVH) and neurocognitive function (e.., verbal memory). The findings may deepen our understanding of the NAcc in the pathology of schizophrenia with AVH and might be a biomarker of clinical effect for rTMS treatment in schizophrenia.